Ciudadania, el poder local e controle do Estado - Angela Moulin Simões Penalva Santos (El Colegio Mexiquense, A.C., 2004)
Brazilian society is experiencing a population expansion within the context of decentralisation of public policies, from the central government to local institutions. Following this line of thought, in this article we analyse the public expenses in the Brazilian Federation in the period 1996-1998 in order to identify the institutions that have assumed the financial right of the citizens, as well as to estimate if there has been a transfer of responsibilities among federal institutions. The success of this process is related to the integrated performance of the external control from the public administration. In that sense, we also study the control exercised by Parliaments, Administrative Courts, Public Prosecution Offices and the Judicial Power beyond social control, taking into consideration their improvement and highlighting the control of the Public Prosecution Office as well as the control exercised by the popular councils.